2014
DOI: 10.1016/j.ajog.2014.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Brief interventions for illicit drug use among peripartum women

Abstract: We review the evidence and identify limitations of the current literature on the effectiveness of brief interventions (≤5 intervention sessions) on illicit drug use, treatment enrollment/retention, and pregnancy outcomes among pregnant and postpartum women; and consider this evidence in the context of the broader brief intervention literature. Among 4 published studies identified via systematic review and meeting a priori quality criteria, we found limited, yet promising evidence of the benefit of brief interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…30,31 The majority of existing interventions have had a single focus either on reducing alcohol/drug use or improving sexual health, and very few of these have targeted pregnant women exclusively. 20,[32][33][34] A single session brief intervention targeting sexual risk reduction in a sample of men and women patients at a STI clinic found that a Results of clustered logistic regression using data from both time points. b Results of logistic regression on follow-up engagement only, time and time • group terms not applicable.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 The majority of existing interventions have had a single focus either on reducing alcohol/drug use or improving sexual health, and very few of these have targeted pregnant women exclusively. 20,[32][33][34] A single session brief intervention targeting sexual risk reduction in a sample of men and women patients at a STI clinic found that a Results of clustered logistic regression using data from both time points. b Results of logistic regression on follow-up engagement only, time and time • group terms not applicable.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the efficacy of SBIRT for pregnant women, especially for decreasing alcohol use and tobacco use (Bowden, Oag, Smith, & Miller, 2010; Chang et al, 2005; Chang, Wilkins-Haug, Berman, & Goetz, 1999; Ferreira-Borges, 2005; O’Connor & Whaley, 2007). In addition, a recent systematic literature review of randomized clinical trials on the efficacy of brief interventions for illicit drug use in pregnancy found limited but promising results (Farr, Hutchings, Ondersma, & Creanga, 2014).…”
Section: Conceptual Framework and Methodsmentioning
confidence: 99%
“…Taking patient histories and using verbal screening tools provide the opportunity for the prenatal care clinician to offer brief intervention or motivational interviewing (6,20). Brief behavioral counseling interventions have been shown to be effective in reducing drinking (21,22), smoking (23,24), and illicit drug use (25) during pregnancy and to improve pregnancy outcomes (26). However, more than half of respondents in our study reported a low frequency of conducting brief intervention or performing motivational interviewing or cognitive behavioral therapy, potentially due to the time-consuming nature of these activities or referral to treatment centers or addiction specialists.…”
Section: Commentmentioning
confidence: 77%